PERSEPSI PETANI TERHADAP SYARAT-SYARAT PENTING UNTUK MENDAPATKAN PEMBIAYAAN - Amalia Prasiwi; Eliana Wulandari (Universitas Tadulako, 2018)
The purpose of this study was to analyze farmers’ perception on the requirements to access financing from banks, micro financing institutions, farmers’ associations, traders, and agricultural input kiosks. This study used collateral, character, capacity, capital, condition of economy, loan size, farmer ability, farm size, spouse knowledge, membership, and sales contract as variables. Based on the Cartesian diagram, the variables included in the first quadrant areactually the important requirements for financing providers, but were considered not important by the farmers and those included in the second quadrant are the requirements which were important for both the financing providers and the farmers. The variables included in the third quadrant are the requirements which werenot important for both the finance providers and the farmers whereas those included in the fourth quadrant are the requirements which werenot important for financing providers, but was not actually considered important for the farmers.Keywords: Farmer knowledge, finance requirements, and IPA